Thermally driven structural phase transformation and dislocation density of CdS nanoparticles precipitated without surfactant in KOH alkaline medium: DOI: 10.48129/kjs.11913 - Chan Kok Sheng; Alrababah, Yousef Mohammad (Kuwait Journal of Science, 2022)
The present research demonstrates a detailed discussion for the effect of annealing temperature on the structural transformation and surface morphology of the CdS nanoparticles synthesized using the precipitation method without surfactant in KOH alkaline medium. The annealing temperature used was in the range of 160 – 480 oC. The samples structural, functional group and morphological properties were investigated by using XRD, FTIR and SEM techniques. XRD analysis reveals that the CdS has gradually been transformed from the pure cubic to hexagonal polycrystalline structure as well as improved crystallinity upon increasing the temperature. Besides, the parameters of average crystallite size and dislocation density were calculated using the established Debye-Scherrer equation. The average crystallite size was in nano-dimension and increases gradually with temperature. The FTIR spectra indicate that the characteristic vibration band of CdS emerged in the lower wavenumber region of 650 and 500 cm-1, and the band becomes stronger as the temperature rises. Also, the SEM images demonstrate that the CdS exhibits uniform spherical morphology and the particle size grows larger at elevated temperatures. The improved crystallinity and structural properties tuning ability against temperature allows beneficial optical applications as solar cells, photocatalysts, non-linear optics, light emitting diodes and optoelectronic devices.